Unconstitutional supranational arrangements for patent law: leaving out the elected legislators and the people's participatory rights. Issue 2 (4th May 2019) - Xenos, Dimitris
ABSTRACT: Substantive economic law in the context of patents creates industrial property rights and monopolies in almost all fields of technology, affecting considerably the economic and social well-being of the state and its people. The mass nationalisation of the international patents of the European Patent Office (EPO) has long raised serious questions about democratic control, in view of the reality that most of its patents are taken by large companies and corporations from a small number of states, mostly from outside the EU. The EU has recently expanded this system by creating a federal (unitary) patent framework consisting of the EPO and a new international court, the Unified Patent Court (UPC), that abolishes the already limited national control. But how can national control ever be totally abolished, especially in such an important social–economic context? And, can the EU exercise effective democratic control of the federal system that it has created? The observed constitutional asymmetries of a federal/unitary patent system that is created in the absence of a federation and is based on two non-EU bodies (EPO, UPC) no longer guarantee the democratic participatory rights of the people for whose benefit economic rules and property rights are justified, regulated and applied.